Hambatan Menulis Biografi dalam Keterbatasan Akses Digital di MAN 2 Karawang - Keyshya Alaika Rahmadayanthi; Jesicka Sukmaya; Echa Salsabila; Azahra Nurfitriani; Sutri Sutri (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2026)
This study aims to determine and analyze in depth the obstacles to writing biographical texts within a learning ecosystem characterized by limited digital access at MAN 2 Karawang. This field research employed a descriptive qualitative approach. Data were gathered through structured classroom observations and in-depth interviews with Indonesian language teachers and student representatives, which were subsequently analyzed using the Miles and Huberman interactive model. The findings reveal three primary obstacles, which consist of delays in fact-verification due to the lack of school digital archives, inflated instructional time allocation resulting from reliance on manual print exploration, and narrative discontinuities caused by limited online communication with sources. Nevertheless, these technological infrastructure constraints paradoxically drive students toward reflective thinking, enhance linguistic mechanics in manual writing, and deepen the internalization of the subject's moral values rather than merely copying raw data from the internet. This study concludes that success in biography-writing competency is not linearly dependent on technological advancement, but is instead determined by educators' creative adaptability in transforming limited information into a deeply contemplative offline learning experience.